PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR HEALTHCARE YANG TERDAFTAR DI BURSA EFEK INDONESIA - ,; , (Bilancia : Jurnal Ilmiah Akuntansi; Vol 7 No 1 (2023): Bilancia : Jurnal Ilmiah Akuntansi, 2023)
ABSTRACT This   study   aim   to   examines   and   analyze   the   effect   of   financial   performance   that   is   projected   with   financial   ratios   in   the   form   of   quick   ratio   (QR),  total   asset   turnover   (TATO),  net   profit   margin   (NPM),  earning   per   share  (EPS),  price   to   earning   ratio  (PER), and  price   to   book   value  (PBV)  on   stock   price.   The   type   of   research   used   is   quantitative  asosiatif   research.   Data   collection   technic   used   is   documents   review.   The   data   source   derived   from   secondary   data   of   annual   financial   report   and   annual   closing   price   of   stock.   The   population   of   this   study   is   healthcare   sector   companies   listed  on   the   Indonesian   Stock   Exchange   totaling   24   companies.   50   samples   in   this   study   were   selected   by   purposive   sampling  method   and   analyzed   using   panel   data   regression. The   result   showed   that   QR, TATO ,   and   NPM   had   no   positive   significant   effect   on   stock   price,   EPS  and   PER   had   positive  l and   no  significant   effect   on   stock   price,   while  PBV   had    positive   significant   effect   on   stock   price.   The   study   result   imply   that   investors   of   healthcare   sector   companies   listed   on   the   Indonesian   Stock   Exchangenot   not   paying   attention   to   QR, TATO,  NPM,  EPS,  PER ,   except   P BV   in   terms   of   making   decision   to   buy   stock   price. Keywords: Stock Price, Financial Performance, Financial Ratio